TINJAUAN KRIMINOLOGI TERHADAP PORNOGRAFI YANG DIPERJUALBELIKAN MELALUI MEMBER VIP MEDIA SOSIAL TELEGRAM - Damanik, Vania Andari (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2023)
This study aims to determine the factors that cause pornography crimes that are traded through telegram social media VIP members, efforts to deal with pornography crimes that are traded through Telegram social media VIP members, as well as legal sanctions against pornography traded through telegram social media VIP members. This thesis uses empirical legal research methods. Research data were collected by means of document/library study and distribution of questionnaires as well as interviews. The results of the study show that the factors that cause pornography crimes that are traded through social media telegrams carried out by VIP members are internal and external factors. Internal factors are curiosity (84.2%) and only for entertainment 36.8%, then external factors are factors influenced by friends (5.3%). Then, in this case, the Department of Communication and Informatics of Medan City is taking preventive measures, namely in the form of a pornographic content complaint service provided by the Ministry of Communication and Informatics and the blocking of content related to pornography. then legal sanctions against pornography that is traded through VIP members in Islamic Criminal Law can be subject to jarimah ta'zir. Then it is regulated in the Pornography Law Number 44 of 2008 Chapter VII concerning "CRIMINAL PROVISIONS" in Article 31, Article 32, Article 36.